IMPROVING SPEAKING SKILLS OF SECONDARY SCHOOL LEARNERS - Abduraxmonov Komiljon Mamurjon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
The article touches upon the topical issue of creating the aptitudes of talking a foreign dialect among understudies of a common instruction school within the setting of distance learning. As an arrangement to the issue of creating verbal discourse aptitudes in a foreign language, the creator proposes to present authentic poetic materials into the method of teaching a remote dialect within the classroom, gives the stages and strategies of working with them utilizing the illustration of one lyric, additionally proposes author’s works out created on the basis of the utilize of true lovely texts.